Evaluation of safety climate and employee injury rates in healthcare. Issue 9 (27th April 2016) - Cook, Jacqueline M; Slade, Martin D; Cantley, Linda F; Sakr, Carine J
Abstract : Objectives: Safety climates that support safety-related behaviour are associated with fewer work-related injuries, and prior research in industry suggests that safety knowledge and motivation are strongly related to safety performance behaviours; this relationship is not well studied in healthcare settings. Methods: We performed analyses of survey results from a Veterans Health Administration (VHA) Safety Barometer employee perception survey, conducted among VHA employees in 2012. The employee perception survey assessed 6 safety programme categories, including management participation, supervisor participation, employee participation, safety support activities, safety support climate and organisational climate. We examined the relationship between safety climate from the survey results on VHA employee injury and illness rates. Results: Among VHA facilities in the VA New England Healthcare System, work-related injury rate was significantly and inversely related to overall employee perception of safety climate, and all 6 safety programme categories, including employee perception of employee participation, management participation, organisational climate, supervisor participation, safety support activities and safety support climate. Conclusions: Positive employee perceptions of safety climate in VHA facilities are associated with lower work-related injury and illness rates. Employee perception of employee participation, management participation, organisational climate, supervisor participation, safety support activities and safety support climate were all associated with lower work-related injury rates. Future implications include fostering a robust safety climate for patients and healthcare workers to reduce healthcare worker injuries.